2022
DOI: 10.1186/s43066-022-00194-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of direct-acting antiviral therapy on metabolic profiles and adiponectin serum level in different categories of patients with chronic hepatitis C infection

Abstract: Background Infection with the hepatitis C virus (HCV) is a worldwide health problem. HCV infection is linked to a variety of metabolic abnormalities as it interferes with lipid metabolism, causing steatosis and a wide range of adipocytokine alterations, as well as impairing glucose metabolism, resulting in a rising prevalence of insulin resistance (IR) and type 2 diabetes. Over the last few years, numerous oral anti-HCV medicines (direct-acting antivirals; DAAs) have been introduced. With DAA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…All patients in our study achieved SVR-12. This success rate is similar to many studies done after the introduction of DAAs [ 18 20 ]. Our study population is selected with a normal baseline metabolic profile, despite being chronically infected by HCV.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All patients in our study achieved SVR-12. This success rate is similar to many studies done after the introduction of DAAs [ 18 20 ]. Our study population is selected with a normal baseline metabolic profile, despite being chronically infected by HCV.…”
Section: Discussionsupporting
confidence: 90%
“…This could be attributed to the baseline metabolic state of their cohort, as two-thirds of the included patients had a hyperlipidemic state prior to treatment [ 4 ]. Another study, in our Ain Shams virology treatment center, done on HCV-infected patients with decreased eGFR (of 30 ml/min or less), they found that after achieving SVR, the triglycerides levels, and HbA1C, were decreased, while the total cholesterol, LDL, and HDL levels were increased [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B) Group that is difficult to treat according to these standards: Having received Peg-INF treatment, having total serum bilirubin levels greater than 1.2 mg/dL, serum albumin levels lower than 3.5 g/dL, having an INR greater than 1.2, and having a platelet count below 150,000/mm3. This group is eligible to get a 12-week course of sofosbuvir, daclatasvir, and ribavirin treatment ( Allam et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%